2014
DOI: 10.1111/eth.12233
|View full text |Cite
|
Sign up to set email alerts
|

Does it Pay to Care?: Exploring the Costs and Benefits of Parental Care in the Hibiscus Harlequin BugTectocoris diophthalmus(Heteroptera: Scutelleridae)

Abstract: Knowledge of the selective pressures favouring parental care can inform our understanding of the evolutionary origins and transitions of sociality in insects. Here, we report upon investigations designed to estimate the costs and benefits of parental care in the egg-guarding hibiscus harlequin bug Tectocoris diophthalmus (Heteroptera: Scutelleridae). We found that the presence of a guarding female had no effect on hatching success under benign laboratory conditions. In the wild, however, guarding decreased the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…The evolution of paternal care in hemipteran lineages has been driven by a complex of factors. It probably originated as a response to pressure from predators and parasitoids [ 43 , 71 76 ], to prevent eggs from desiccation [ 77 , 78 ], to develop a more elaborate manipulation of tradeoffs between air exchange and desiccation in water bugs [ 79 – 82 ], or to represent an adaptation to unstable or ephemeral food resources in cydnid families [ 25 , 27 , 32 , 83 , 84 ]. In treehoppers, maternal care is associated with changes from a solitary to gregarious life history in connection with the acquisition of ant mutualism [ 2 , 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…The evolution of paternal care in hemipteran lineages has been driven by a complex of factors. It probably originated as a response to pressure from predators and parasitoids [ 43 , 71 76 ], to prevent eggs from desiccation [ 77 , 78 ], to develop a more elaborate manipulation of tradeoffs between air exchange and desiccation in water bugs [ 79 – 82 ], or to represent an adaptation to unstable or ephemeral food resources in cydnid families [ 25 , 27 , 32 , 83 , 84 ]. In treehoppers, maternal care is associated with changes from a solitary to gregarious life history in connection with the acquisition of ant mutualism [ 2 , 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Adult and nymph shield bugs generally share similar morphology, diet, microhabitat and thus likely share similar predation pressures. In fact, many species from the family Scutelleridae ( jewel bugs) are known to exhibit maternal care, and so adults and nymphs are found in close proximity [29,30]. A distinctive trait of shield bugs is the presence of defensive secretions in both adults and nymphs to deter predators [16,27,28,31].…”
Section: Methods (A) Study Systemmentioning
confidence: 99%
“…The offspring of subsocial invertebrates are potentially vulnerable to predators and/or parasitoids, but they are effectively protected against these enemies by their male and/or female parents (Tallamy & Wood, 1986;Costa, 2006;Trumbo, 2012). For example, among various terrestrial insects, orphaned eggs and young nymphs consistently undergo severe predation pressure, and attendance by parent females greatly enhances their survival (Tallamy & Denno, 1981;Gilbert et al, 2010;Giffney & Kemp, 2014). Female removal experiments have shown that parental defence is highly effective under field conditions, with survival Correspondence: Shin-ya Ohba, Biological Laboratory, Faculty of Education, Nagasaki University, 1-14 Bunkyo-machi, Nagasaki 852-8521, Japan.…”
Section: Introductionmentioning
confidence: 99%